Attitudes of dental professional staff and auxiliaries in Riyadh, Saudi Arabia, toward disclosure of medical errors - Nora S. Al-Nomay; Abdulghani Ashi; Aljohara Al-Hargan; Abdulaziz Alshalhoub; Emad Masuadi (Elsevier, 2017)
Aim: To collect empirical data on the attitudes of dental professionals and dental auxiliaries in Riyadh, Saudi Arabia, regarding the disclosure of medical errors. Methods: A cross-sectional study was conducted, involving the administration of a questionnaire to a sample of 586 participants recruited from over 10 government and private dental institutions in Riyadh between August 2015 and January 2016. The questionnaire collected information regarding participant opinions on (a) personal beliefs, norms, and practices regarding medical errors, (b) the nature of errors that should be disclosed, and (c) who should disclose errors. Results: Most (94.4%) participants preferred that medical errors should be disclosed. However, personal preferences, perceptions of the norm and current practices with respect to which type (seriousness) of error should be disclosed were inconsistent. Only 17.9% of participants perceived that it was the current practice to disclose errors resulting in "Major harm". Over 68% of respondents reported a personal belief, a perception of the norm and a perception of current practice that errors should be disclosed by the erring dentist. Participants at government institutions were more likely to disclose errors than those at private institutions. There were also significant differences in the responses with respect to gender, age, and nationality. The implications for the development of guidelines to help Saudi dentists adopt ethical courses of action for the disclosure of errors are considered. Conclusions: (1) The majority of participants personally believed that errors should be disclosed, (2) there was little agreement between participant personal beliefs and perceptions of the norm and practice with respect to which type of errors should be disclosed, (3) there was strong agreement that the erring dentist is responsible for reporting errors, and (4) the attitudes of the participants varied with respect to type of institution, age, gender, and nationality. Keywords: Medical error, Dental error, Disclosure of medical error, Medical ethics